Metal ion cooperativity in ribozyme cleavage of RNA - Brännvall, Mathias (The National Academy of Sciences, 2001)
Combinations of chemical and genetic approaches were used to study the function of divalent metal ions in cleavage of RNA by the ribozyme RNase P RNA. We show that different divalent metal ions have differential effects on cleavage site recognition and rescue of cleavage activity by mixing divalent metal ions that do not promote cleavage by themselves. We conclude that efficient and correct cleavage is the result of cooperativity between divalent metal ions bound at different sites in the RNase P RNA-substrate complex. Complementation of a mutant RNase P RNA phenotype as a result of divalent metal ion replacement is demonstrated also. This finding together with other data indicate that one of the metal ions involved in this cooperativity is positioned near the cleavage site. The possibility that the Mg(2+)/Ca(2+) ratio might regulate the activity of biocatalysts that depend on RNA for activity is discussed.